Distance and Microsphere Aggregation- Based DNA Detection in a Paper-Based Microfluidic Device - Kalish, Brent; Zhang, Jianhou; Edema, Hilary; Luong, James; Roper, Jenna; Beaudette, Chad; Echodu, Richard; Tsutsui, Hideaki (SLAS TECHNOLOGY: Translating Life Sciences Innovation, 2020)
In paper-based microfluidics, the simplest devices are colorimetric, giving qualitative results. However, getting quantitative data can be quite a bit more difficult. Distance-based devices provide a user-friendly means of obtaining quantitative data without the need for any additional equipment, simply by using an included ruler or calibrated markings. This article details the development of a quantitative DNA detection device that utilizes the aggregation of polystyrene microspheres to affect the distance that microspheres wick through filter paper. The microspheres are conjugated to single-stranded DNA (ssDNA) oligomers that are partially complementary to a target strand and, in the presence of the target strand, form a three-strand complex, resulting in the formation of aggregates. The higher the concentration of the target strand, the larger the aggregate, and the shorter the distance wicked by the microspheres. This behavior was investigated across a wide range of target concentrations and under different incubation times to understand aggregate formation. The device was then used to successfully detect a target strand spiked in extracted plant DNA.
Keywords: Distance-based; Microsphere; Aggregation; DNA detection; Paper-based